Engineered proteins and three-dimensional printing of living materials. (December 2020) - Gona, Ram Surya; Meyer, Anne S.
Abstract: Abstract : Additive manufacturing is a revolutionary three-dimensional (3D) printing technology that has applications in a vast number of fields from aerospace to biological engineering. In the field of bioengineering, it was recently discovered that the principles used in 3D bioprinting of organs and tissues could also be used to 3D print biological materials produced by genetically engineered bacteria. This new technology requires the development of modified bio-ink and optimized printing parameters to promote bacterial physiology while allowing printability. In this article, we highlight the recent advancements in additive manufacturing of engineered living materials using bacteria and their potential applications. We will discuss recent progress and significance of additive manufacturing of proteins and polypeptides produced in situ by engineered bacteria to make multifunctional materials. Finally, we discuss the challenges and prospects of this technology and highlight some of the biomaterials that may benefit from additive manufacturing with bacteria.